2019
DOI: 10.1542/hpeds.2018-0193
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Home Antimicrobial Therapy: OPAT Versus Oral Therapy

Abstract: BACKGROUND: There is increasing evidence that outpatient parenteral antimicrobial therapy (OPAT) is overused for children and that outcomes with oral therapy are equivalent. Our objective was to compare economic burden between OPAT and oral therapy, accounting for direct and indirect costs and caregiver quality of life (QoL). METHODS: We conducted a prospective cohort study of caregivers for children after hospitalization who were treated with prolonged antimicrobial therapy. We collected data about missed wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The overuse of OPAT demonstrates a clear need for further health outcomes research in children. Although previous studies have established the safety and cost-effectiveness of OPAT, the current study by Krah et al 14 highlights the potentially negative patient and caregiver experiences associated with pediatric OPAT. While we await additional health outcomes research studies, hospitalists should continue to collaborate with ID-trained physicians to minimize unnecessary OPAT and optimize oral antibiotics when appropriate.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The overuse of OPAT demonstrates a clear need for further health outcomes research in children. Although previous studies have established the safety and cost-effectiveness of OPAT, the current study by Krah et al 14 highlights the potentially negative patient and caregiver experiences associated with pediatric OPAT. While we await additional health outcomes research studies, hospitalists should continue to collaborate with ID-trained physicians to minimize unnecessary OPAT and optimize oral antibiotics when appropriate.…”
mentioning
confidence: 70%
“…findings reported by Krah et al 14 are an important reminder to OPAT prescribers that the direct and indirect costs of the outpatient administration of IV therapy must be considered at the point of prescribing.…”
mentioning
confidence: 77%
“…Beyond the minimization of line placement and healthcare exposure, COpAT is accompanied by other significant benefits. A study of pediatric patients comparing economic and patient-related benefits of those receiving COpAT with those receiving OPAT found COpAT was associated with significantly lower direct costs of therapy, less missed school for children, less missed work for caregivers, a higher level of caregiver comfort with the planned regimen, and better caregiver quality of life [ 11 ]. Multiple studies have evaluated the impact of the use of oral antimicrobials or implementation of protocols allowing for the use of oral antibiotics in the treatment of bone and joint infections [ 12 •, 13 ].…”
Section: Regimen Redesign From Opat To Copatmentioning
confidence: 99%
“…Line infections, clots, mechanical problems, and general discomfort complicate PICCs, which led to their removal in more than 20% of children in one study 1 . Oral antibiotics avoid these complications and are less burdensome to families 2 . Recently, a series of multicenter studies showed no difference in outcomes between oral and postdischarge intravenous antibiotic therapy (PD‐IV) for complicated appendicitis, osteomyelitis, and complicated pneumonia 3‐5 …”
mentioning
confidence: 99%
“…1 Oral antibiotics avoid these complications and are less burdensome to families. 2 Recently, a series of multicenter studies showed no difference in outcomes between oral and postdischarge intravenous antibiotic therapy (PD-IV) for complicated appendicitis, osteomyelitis, and complicated pneumonia. [3][4][5] Despite a growing body of evidence suggesting that oral therapy ought to be the default treatment strategy rather than PD-IV, the extent to which practices have changed is unknown.…”
mentioning
confidence: 99%